Southeast Asian affairs - Institute of Southeast Asian Studies (Institute of Southeast Asian Studies, 1974)
Contains contributions by experts that discuss the significant issues and events of the year in each of the Southeast Asian nations and the region as a whole.
Keywords: 15.75 history of Asia; 74.21 geography of Asia; Politics and government : Southeast Asia; Economic conditions : Southeast Asia; Länderforschung; Südostasien; ASEAN-Staaten; POLITICAL CONDITIONS; ECONOMIC CONDITIONS; SOCIAL CONDITIONS; SOUTHEAST ASIA; Southeast Asia : Periodicals; Asie du Sud-Est : Périodiques; Southeast Asia; 5.500; South-east Asia : Political events : Serials